2021
DOI: 10.1128/iai.00108-21
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Interference To Inducibly Repress Gene Expression in Chlamydia trachomatis

Abstract: The ability to inducibly repress gene expression is critical to the study of organisms, like Chlamydia, with reduced genomes wherein the majority of genes are likely to be essential. We recently described the feasibility of a CRISPR interference system to inducibly repress gene expression in Chlamydia trachomatis. However, the initial system suffered from some drawbacks, primarily leaky expression of the anhydrotetracycline (aTc) inducible dCas9 ortholog and plasmid instability, that prevented population-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 31 publications
2
76
0
Order By: Relevance
“…An alternative hypothesis that may explain our findings is offered by recent evidence obtained by Ouellette et al (2021) who found that introducing a weak ribosome binding site overcomes leaky protein expression from the tet promoter 63 . Further testing and optimisation of riboswitches in Chlamydia is needed to resolve this, and alternative riboswitch designs (and perhaps a Chlamydia -specific riboswitch) may be required if they are to offer an alternative to the tet promoter for inducible protein expression in Chlamydia .…”
Section: Discussionmentioning
confidence: 79%
“…An alternative hypothesis that may explain our findings is offered by recent evidence obtained by Ouellette et al (2021) who found that introducing a weak ribosome binding site overcomes leaky protein expression from the tet promoter 63 . Further testing and optimisation of riboswitches in Chlamydia is needed to resolve this, and alternative riboswitch designs (and perhaps a Chlamydia -specific riboswitch) may be required if they are to offer an alternative to the tet promoter for inducible protein expression in Chlamydia .…”
Section: Discussionmentioning
confidence: 79%
“…The latter is supported by the fact that a previous large mutagenesis screen did not isolate nonsense mutations for ct006 [ 24 ]. The recent development of a CRISPR interference system enabling induced and transient repression of chlamydial genes [ 51 ] should help clarifying this issue but this is beyond the scope of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“… 2018 , Keb and Fields 2020 ) or CRISPR interference (Ouellette 2018 , Ouellette et al . 2021 ) in case dksA Ct is essential to C. trachomatis intracellular replication and/or developmental transitions. Mechanistic understanding of how DksA Ct functions in C. trachomatis biology will require analysis of whether the protein directly influences pathogen gene expression by binding to RNAP akin to prototypical DksA proteins, or whether DksA Ct is associated with a different mechanism of action, such as interfering with the binding of another protein to RNAP, thus indirectly affecting transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%